Living with HIV: Men's feelings - Mirian Dias dos Santos (2022)
Introduction: Despite advances in health services in providing prevention technologies, the incidence of HIV in the Brazilian population continues to increase, especially in males. In view of this finding, it is possible to observe the difficulty that these people face in their daily lives in relation to treatment and support networks. Thus, this research started from the following question: “What are the experiences and meanings of being diagnosed and living with HIV and the implications for everyday life?” Objectives: To understand the feelings of men living with HIV. Method: Qualitative research, carried out through semi-structured interviews with 35 men who are monitored at a Specialized Assistance Service for HIV/AIDS in the interior of the state of São Paulo, Brazil. The contents of the interviews were submitted to content analysis, in the thematic mode. Results: The analysis made it possible to emerge three themes related to feelings, namely, fear, guilt and loneliness. Conclusion: The serological condition brought the need to deal with different situations, and the reorganization of this phase leads to a change in the meaning of life. It was identified as a learned knowledge that HIV has no face, thus, the relaxation of protection measures are practices that should not occur, although they are neglected. Health education was considered a powerful strategy to expand knowledge for disease prevention and health promotion, especially with regard to the transmission of HIV and other Sexually Transmitted Infections. In this sense, the importance of bonding and welcoming health professionals was highlighted.